The cost of equity in emerging markets : the Latin American case - Garay, Urbi; González, Maximiliano; Rosso Murillo, John William (Editorial Universidad Pedagógica y Tecnológica de Colombia, 2021)
Eng: In this book, we estimate the differences between expected (predicted) cost of equity generated, by nine methods of the discount rate proposed in the literature, and observed stock returns (as proxied by observed total stock returns), and then determine whether these differences can be explained by country and industry factors.